2018
DOI: 10.3389/fnana.2018.00069
|View full text |Cite
|
Sign up to set email alerts
|

Basal Forebrain Nuclei Display Distinct Projecting Pathways and Functional Circuits to Sensory Primary and Prefrontal Cortices in the Rat

Abstract: Recent evidence supports that specific projections between different basal forebrain (BF) nuclei and their cortical targets are necessary to modulate cognitive functions in the cortex. We tested the hypothesis of the existence of specific neuronal populations in the BF linking with specific sensory, motor, and prefrontal cortices in rats. Neuronal tracing techniques were performed using retrograde tracers injected in the primary somatosensory (S1), auditory (A1), and visual (V1) cortical areas, in the medial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…The distinct early sensory modulation effects of cholinergic and GABAergic BF neurons observed in this study might therefore be owed to the different functions of these two basal forebrain systems. Here we targeted cholinergic and GABAergic projections neurons located primarily in the same area (HDB) since previous publications have shown that populations from different basal forebrain centers can have heterogeneous effects 81 . However, we cannot exclude that the effects observed during GABAergic fiber stimulation were, at least partially, derived from GABAergic fibers originating in the MCPO, a nucleus containing a majority of GABAergic bulbopetal neurons 23,25,47,115 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct early sensory modulation effects of cholinergic and GABAergic BF neurons observed in this study might therefore be owed to the different functions of these two basal forebrain systems. Here we targeted cholinergic and GABAergic projections neurons located primarily in the same area (HDB) since previous publications have shown that populations from different basal forebrain centers can have heterogeneous effects 81 . However, we cannot exclude that the effects observed during GABAergic fiber stimulation were, at least partially, derived from GABAergic fibers originating in the MCPO, a nucleus containing a majority of GABAergic bulbopetal neurons 23,25,47,115 .…”
Section: Resultsmentioning
confidence: 99%
“…The basal forebrain is critical for many cognitive processes [65][66][67][68][69] as well as for sensory information processing 51,[70][71][72][73][74][75] . Despite longstanding knowledge about the heterogeneity of BF derived long-range projections 17,25,76,77 , studies examining their function in sensory processing so far have been focused almost exclusively on cholinergic projections 3,27,28,46,[78][79][80][81][82] .…”
Section: Discussionmentioning
confidence: 99%
“…Viral vectors containing inverted DNA constructs encoding DREADDs were stereotactically injected in the right BFB ( Figure 1 ). Since cholinergic neurons in the anterior medial portion of the BFB have been shown to project to the medial and frontal cortex, and have been implicated to play a role in attention, these medial nuclei were targeted during the stereotactic surgery ( Ballinger et al., 2016 ; Chaves-Coira et al., 2018 ). Immunohistochemical experiments were performed on eight animals to validate transfection of cholinergic neurons in the target region.…”
Section: Resultsmentioning
confidence: 99%
“…The prefrontal cortex receives cholinergic innervation from basal forebrain and laterodorsal/pedunculopontine tegmentum (Saper and Loewy, 1982;Vincent et al, 1983;Satoh and Fibiger, 1986;Chaves-Coira et al, 2018), both of which have wake-active and REM sleep-active neurons (Lee et al, 2005;Sakai, 2012;Boucetta et al, 2014). Although the role of prefrontal ACh from either of these sources in triggering the onset of wake state is not clear, recent optogenetic studies showed that the stimulation of basal forebrain cholinergic neurons induced wakefulness (Irmak and de Lecea, 2014;Xu et al, 2015) whereas the stimulation of PPT cholinergic neurons primarily increased REM sleep (Van Dort et al, 2015).…”
Section: Discussionmentioning
confidence: 99%